THE RIGHTS AND OBLIGATIONS OF THE GUARDIANSHIP AND TRUSTEESHIP AUTHORITIES AND THE ORGANIZATION OF ACTIVITIES IN THIS FIELD - Choriyeva Xurshidabonu Xurram kizi (Scholar Express Journals, 2024)
This article analyzes the general rules of the organization of guardianship and trusteeship, the legal foundations of this institution, as well as the grounds for establishing guardianship and trusteeship and their rights and obligations in this field. The legal grounds for becoming a guardian and trustee are given, as well as the ideas and views of scientists on this matter. Opinions were expressed on the issues of the institution of guardianship and trusteeship in the new Uzbekistan. The conclusions were made based on the opinions presented in the article, the studied scientific sources, and the research conducted by scientists in this regard.
Keywords: guardian; trustee; general grounds; partially capable person.